2020
DOI: 10.5155/eurjchem.11.4.342-350.2045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into propane dehydrogenation into propylene over chromium (III) oxide by cluster approach and Density Functional Theory calculations

Abstract: A preliminary study to provides insight into the kinetic and thermodynamic assessment of the reaction mechanism involved in the non-oxidative dehydrogenation (NOD) of propane to propylene over Cr2O3, using a density functional theory (DFT) approach, has been undertaken. The result obtained from the study presents the number of steps involved in the reaction and their thermodynamic conditions across different routes. The rate-determining step (RDS) and a feasible reaction pathway to promote propylene production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The structures were built and minimised using the molecular mechanics (MMFF) method to remove strain energy, 38,89 after which the resulting structure was used as initial geometry during the use of DFT where B3LYP calculation method with 6-31G* and LANL2DZ basis sets were adopted, in line with the existing reports. 29,31 In using semi-empirical theory, the PM3 method was also used to optimise another set of the built structures where respective minimised structures were used as the structure for initiating the PM3 semi-empirical calculation. Existing literature 40,41 has justified using the PM3 and B3LYP method for the chromium and transition metals-based systems.…”
Section: Computational Methodology Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures were built and minimised using the molecular mechanics (MMFF) method to remove strain energy, 38,89 after which the resulting structure was used as initial geometry during the use of DFT where B3LYP calculation method with 6-31G* and LANL2DZ basis sets were adopted, in line with the existing reports. 29,31 In using semi-empirical theory, the PM3 method was also used to optimise another set of the built structures where respective minimised structures were used as the structure for initiating the PM3 semi-empirical calculation. Existing literature 40,41 has justified using the PM3 and B3LYP method for the chromium and transition metals-based systems.…”
Section: Computational Methodology Detailsmentioning
confidence: 99%
“…It was further reported that the reaction paths with moderate chromium site participation favoured better selectivity for propylene production. 31 The report of Hus et al 37 further indicated that high temperature, high pressure, and prolonged propylene accumulation on the catalyst promotes its deactivation. These reports suggest the need to investigate the impact of substituting the chromium site with other metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation